A House Divided: Threat Perception, Military Factionalism, and Repression in Africa. (September 2017) - Hendrix, Cullen S.; Salehyan, Idean
Why do African regimes repress certain contentious challenges but not others? We argue that in addition to opposition claims and tactics, African regimes are especially likely to view challenges expressing ethnic and/or religious claims as threatening. However, in theorizing the decision to use repression, we relax the assumption that the state is a unitary actor. Leaders with a history of factionalism in their security forces face a delegation problem: orders to repress may not be followed or could even cause intraregime violence and/or defections. For this reason, states with divided security forces are less likely to enact repression. This potential for fracturing the regime will be greatest when the challenge has ethnic or religious claims and targets the state, implying an interactive effect. Using the Social Conflict in Africa Database, we find that regimes with a history of past military factionalism are generally less likely to use repression and are especially less likely to repress contentious challenges making ethnic or religious claims.